2022
DOI: 10.3389/fpsyt.2022.863999
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility and Effectiveness of a Novel, On-Line Social Skills Intervention for Individuals With Prader-Willi Syndrome

Abstract: IntroductionPeople with neurodevelopmental disabilities, including Prader-Willi syndrome (PWS), are at heightened risk for the negative sequalae of loneliness, including depression and anxiety. While societal factors such as stigma or limited social opportunities contribute to loneliness, so too do deficits in social cognition and social skills. People with PWS have specific difficulties recognizing affect in others, accurately interpreting social interactions, and taking the perspectives of others. These feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Recently, two studies reported promising results on two online intervention programs aimed at developing social skills. The BOSS program ( 50 ) was offered to adolescents and young adults with PWS. The sessions were collective and took place by videoconference, 3 times a week for 10 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two studies reported promising results on two online intervention programs aimed at developing social skills. The BOSS program ( 50 ) was offered to adolescents and young adults with PWS. The sessions were collective and took place by videoconference, 3 times a week for 10 weeks.…”
Section: Introductionmentioning
confidence: 99%